Improving the international monetary system : constraints and possibilities - Mussa, Michael...[et al] (IMF WashingtonUS, 1994)
Addresses major policy issues associated with the future of the international monetary system. Focuses on whether there is a need for fundamental reform of this system and discusses reforms that could strengthen and improve the system.